Effect of Dry Heating on Some Physicochemical Properties of Protein-Coated High Amylose and Waxy Corn Starch - Lili Mao; Pranita Mhaske; Asgar Farahnaky; Mahsa Majzoobi (Foods, 2023)
The dry heat treatment (DHT) of starch and hydrocolloid mixtures is gaining acknowledgement since hydrocolloids can enhance the efficiency of DHT. However, the DHT of a starch–protein mixture has been less investigated. In this study, the effects of different proteins including sodium caseinate (SC), gelatin, and whey protein isolate (WPI) added to high amylose and waxy corn starches (HACS and WCS, respectively) prepared by the dry mixing and wet method before and after DHT were studied. The DHT of both starches with WPI and SC prepared by the wet method increased the peak viscosity, but no change was observed when gelatin was added. Dry mixing of HACS with the proteins did not affect the peak viscosity before and after DHT. The gelatinization temperatures and enthalpy of both starches showed a slight decrease with the addition of all proteins and reduced further after DHT. The firmness, gumminess, and cohesiveness of the samples decreased upon DHT. The SEM results revealed that the granules were coated by proteins and formed clusters. Particle size analysis showed an increase in the particle size with the addition of proteins, which reduced after DHT. Under the conditions used, the wet method was more successful than dry mixing and the effects of WPI > SC > gelatin in enhancing the physicochemical properties of the tested starches after DHT.